Model of Handling People with Mental Disorders through Christian Spiritual Therapy at the Gerasa Rehabilitation Center - Muryati, Muryati; Christanto, Andreas; Tahulending, Matius (Universitas Muhammadiyah Metro, 2022)
Diseases in humans consist of diseases of spirit, body, and soul. Diseases of the Christian faith's spirit are solved by prayer and repentance. Diseases of the body by taking him to the hospital to be treated by medical personnel. While mental illness until now has not had the proper treatment. It needs to do because there are people with mental disorders (ODGJ). This study aims to determine the model and impact of Christian spiritual therapy in dealing with ODGJ patients at the Gerasa rehabilitation center. This research uses the descriptive qualitative method. The results showed that the model of therapy given to ODGJ patients was 1) one year of orientation period; 2) perform worship: prayer, praise worship, and the word of God; pastoral counseling which carried out every day either personally/communally; organize recreation, community service, and sports; and medical treatment. Then the impacts include: 1) behavior change; 2) changes in speech; 3) change of mindset; 4) self-discovery; 5) self-potential development; 6) character change; 7) recovered and allowed to return to the family and get a job.